Clinical diagnosis and management of small fiber neuropathy: an update on best practice. (1st September 2020) - Devigili, Grazia; Cazzato, Daniele; Lauria, Giuseppe
ABSTRACT: Introduction: Small fiber neuropathy (SFN) is a heterogeneous group of disorders affecting thin myelinated Aδ and unmyelinated C fibers. Common symptoms include neuropathic pain and autonomic disturbances, and the typical clinical presentation is that of a length-dependent polyneuropathy, although other distributions could be present. Area covered: This review focuses on several aspects of SFN including etiology, clinical presentation, diagnostic criteria and tests, management, and future perspectives. Diagnostic challenges are discussed, encompassing the role of accurate and standardized assessment of symptoms and signs and providing clues for the clinical practice. The authors discuss the evidence in support of skin biopsy and quantitative sensory testing as diagnostic tests and present an overview of other diagnostic techniques to assess sensory and autonomic fibers dysfunction. The authors also suggest a systematic approach to the etiology including a set of laboratory tests and genetic examinations of sodium channelopathies and other rare conditions that might drive the therapeutic approach based on underlying cause or symptoms treatment. Expert opinion: SFN provides a useful model for neuropathic pain whose known mechanisms and cause could pave the way toward personalized treatments.